Post-approval variations to dossiers for vaccines: analysis of regulatory and methodological approaches used in the Russian Federation and abroad - V. A. Shevtsov; Yu. V. Olefir; V. A. Merkulov; V. P. Bondarev; I. N. Indikova; E. E. Evreinova; A. V. Rukavishnikov; L. M. Khantimirova; D. V. Gorenkov (Регуляторные исследования и экспертиза лекарственных средств)
The management of post-approval changes to registration dossiers for medicinal products is one of the most important factors for ensuring sustainable quality, safety and efficacy of medicines. Competent authorities that use the module format of the registration dossier, i.e. the regulatory authorities of the European Union, USA and other members of the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH), and the Eurasian Economic Union (EEU), issue guidelines on changes to registration dossiers for pharmaceuticals and biologicals (immunological products). Vaccines (finished dosage forms) and vaccine antigens (active ingredients) are a specific group of immunobiological products which have great prophylactic importance for healthcare, and which are associated with challenging development and specific methods of manufacturing and quality control. The procedure of introducing post-approval variations to dossiers for immunobiological medicinal products is poorly reflected in the current Russian and EEU regulations. The World Health Organization (WHO) established a procedure described in the «Guidelines on procedures and data requirements for changes to approved vaccines». The purpose of the present study was to compare current Russian and international legislation in terms of regulatory requirements for post-approval сhanges to dossiers for immunobiological products. The Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products» of the Ministry of Health of the Russian Federation is drafting Guideline on introducing post-approval changes into dossiers for immunobiological medicines. The draft includes a detailed review of various categories of changes based on their importance, and a list of conditions and required documents for specific groups of medicines. This article summarises scientific and methodological approaches to evaluation of changes introduced in registration dossiers for vaccines in order to further improve the regulatory framework of the Russian Federation and the EEU.